The membrane-bound transferrin homologue melanotransferrin: roles other than iron transport? - Sekyere, E.; Richardson, D.R. (FEBS Letters, 2000)
Melanotransferrin (MTf) is a membrane-bound transferrin (Tf) homologue that is found at high levels in melanoma cells. MTf has many characteristics in common with serum Tf and previous studies have shown that it can bind Fe. This has led to speculation that MTf may be involved in Fe transport. Because Fe is required for a variety of metabolic reactions including ATP and DNA synthesis, MTf could play a role in proliferation. However, recently it has been shown that MTf plays very little role in Fe uptake by melanoma cells, and unlike other Fe transport molecules (e.g. the transferrin receptor), its expression is not controlled by Fe. In the present review the function of MTf is discussed in relation to data suggesting other roles apart from Fe uptake.